(untitled) (Research, Society and Development, 2022)
Anxiety disorders are among the most common mental disturbances around the world, and they can negatively impact a patient’s quality of life and disrupt important activities of daily living. Recent studies have shown that the psychopathology of anxiety involves altered neural circuits and the normalization of these circuits would be the key factor for therapeutic effects. Acupuncture has an anxiolytic effect recognized in the treatment of anxiety. However, neural mechanism underlying the anxiolytic acupuncture effect is unknown. Some studies have shown that brain circuits related to the control of the autonomic nervous system, emotional, memory and cognitive processing are modulated by acupuncture. These circuits overlap the circuits related to psychopathology of anxiety. Thus, in this paper, we presented a hypothesis about how the acupuncture can reduces anxiety through modulation of brain circuits. In conclusion, the consulted literature showed that acupuncture has the potential to modulate the brain regions implicated in the anxious behaviors. Nonetheless, future studies should be done to elucidate the neuroendocrine mechanisms of acupuncture in the anxiety disorders.